Hebella venusta - Calder, Dale R. (Zenodo, 2013)
Hebella venusta (Allman, 1877) Fig. 5a Lafoea venusta Allman, 1877: 11, pl. 6, figs. 2, 3. Type locality. USA: Florida, Loggerhead Key (Allman 1877). Voucher material. Bethel Shoal off Vero Beach, 27°42.6’N, 80°06.8’W, 24 m, on Thyroscyphus marginatus , 18.ii.1976, Johnson-Sea-Link , JSL 328, diver lockout, one colony, without gonothecae, coll. S. Nelson, ROMIZ B1097. Remarks . Hebella venusta (Allman, 1877) appears to be common in the Caribbean region (Fraser 1944, as Lafoea venusta Vervoort 1968; Galea 2010; Castellanos Iglesias 2011). The species was collected on Challenger Bank near Bermuda in 1873 during the voyage of H.M.S. Challenger (Ritchie 1909, as Lafoea venusta Calder 1991a), but it has not been seen in that region since then and appears to have become locally extinct (Sterrer 1998; Calder 2000). Records from the Indian Ocean (Ritchie 1910, as Lafoea venusta Mergner & Wedler 1977) need to be verified. Gonothecae of H. venusta were first described by Galea (2010), but the character of the gonophores is still unknown. Reported distribution. Atlantic coast of Florida. First record. Western Atlantic. North Carolina (Cain 1972) to Brazil (Oliveira et al . submitted), including Bermuda (Calder 1991a), the Gulf of Mexico (Calder & Cairns 2009), and the Caribbean Sea (Galea 2010). : Published as part of Calder, Dale R., 2013, Some shallow-water hydroids (Cnidaria: Hydrozoa) from the central east coast of Florida, USA, pp. 1-72 in Zootaxa 3648 (1) on page 17, DOI: 10.11646/zootaxa.3648.1.1, http://zenodo.org/record/5264362 : {"references": ["Allman, G. J. (1877) Report on the Hydroida collected during the exploration of the Gulf Stream by L. F. de Pourtales, assistant United States Coast Survey. Memoirs of the Museum of Comparative Zoology at Harvard College, 5 (2), 1 - 66.", "Fraser, C. M. (1944) Hydroids of the Atlantic coast of North America. University of Toronto Press, Toronto, 451 pp.", "Vervoort, W. (1968) Report on a collection of Hydroida from the Caribbean region, including an annotated checklist of Caribbean hydroids. Zoologische Verhandelingen, 92, 1 - 124.", "Galea, H. R. (2010) Additional shallow-water thecate hydroids (Cnidaria: Hydrozoa) from Guadeloupe and Les Saintes, French Lesser Antilles. Zootaxa, 2570, 1 - 40.", "Castellanos Iglesias, S., Varela, C., Ortiz Toucet, M. & Orozco, M. V. (2011) Los hidrozoos (Cnidaria, Hydrozoa) de la Cayeria sur del Golfo de Batabano, Cuba. Revista Ciencias Marinas y Costeras, 3, 9 - 29.", "Ritchie, J. (1909) Two unrecorded ' Challenger ' hydroids from the Bermudas, with a note on the synonymy of Campanularia insignis. Zoologist, 4 th series, 13, 260 - 263.", "Calder, D. R. (1991 a) Shallow-water hydroids of Bermuda. The Thecatae, exclusive of Plumularioidea. Royal Ontario Museum, Life Sciences Contributions, 154, 1 - 140.", "Sterrer, W. (1998) How many species are there in Bermuda? Bulletin of Marine Science, 62, 809 - 840.", "Calder, D. R. (2000) Assemblages of hydroids (Cnidaria) from three seamounts near Bermuda in the western North Atlantic. Deep-Sea Research I, 47, 1125 - 1139. http: // dx. doi. org / 10.1016 / S 0967 - 0637 (99) 00093 - X", "Ritchie, J. (1910) The marine fauna of the Mergui Archipelago, Lower Burma, collected by Jas. J. Simpson, M. A., B. Sc, and R. N. Rudmose-Brown, D. Sc, University of Aberdeen, February to May 1907. - The hydroids. Proceedings of the Zoological Society of London, 1910, 799 - 825.", "Mergner, H. & Wedler, E. (1977) Uber die Hydroidpolypenfauna des Roten Meeres und seiner Ausgange. \" Meteor \" Forschungs-Ergebnisse, D, 24, 1 - 32.", "Cain, T. D. (1972) Additional epifauna of a reef off North Carolina. Journal of the Elisha Mitchell Scientific Society, 88, 79 - 82.", "Calder, D. R. & Cairns, S. D. (2009) Hydroids (Cnidaria: Hydrozoa) of the Gulf of Mexico. In: Felder, D. L. & Camp, D. K. (Eds.), Gulf of Mexico. Origin, waters, and biota. Vol. 1. Biodiversity. Texas A & M University Press, College Station, pp. 381 - 394."]}